2017
DOI: 10.7161/omuanajas.288862
|View full text |Cite
|
Sign up to set email alerts
|

Determination of grain yield and quality traits of some bread wheat (Triticum aestivum L.) varieties

Abstract: ÖZETGünümüzde kullanım amacına göre, buğdayın tane verimi yanında bazı kalite özelliklerinin de belirlenmesi gerekmektedir. Bu çalışma, Yozgat ekolojik koşullarında 14 farklı ekmeklik buğday çeşidinin verim ve kalite yönünden durumlarını belirlemek amacıyla 2010-2014 yılları arasında yürütülmüştür. Deneme tesadüf blokları deneme desenine göre üç tekrarlamalı olarak gerçekleştirilmiştir. Araştırmada çeşitlerin bitki boyu, tane verimi, bin tane ağırlığı, hektolitre ağırlığı, kül oranı, yağ oranı, protein içeriği… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 16 publications
2
49
0
2
Order By: Relevance
“…Surma et al (2012) also demonstrated that genotype has a greater influence on kernel hardness than environment. On the other hand, many other studies have demonstrated that environmental conditions have a larger effect on protein content than the genetic background (Mut et al 2010). Surma et al (2012) has also shown that the alveograph parameter was influenced to a similar degree by genotype and environment.…”
Section: Discussionmentioning
confidence: 98%
“…Surma et al (2012) also demonstrated that genotype has a greater influence on kernel hardness than environment. On the other hand, many other studies have demonstrated that environmental conditions have a larger effect on protein content than the genetic background (Mut et al 2010). Surma et al (2012) has also shown that the alveograph parameter was influenced to a similar degree by genotype and environment.…”
Section: Discussionmentioning
confidence: 98%
“…The highest yield of red bread wheat varieties was determined as Pehlivan with a rate of 55%. The flour yields obtained from white bread varieties were almost close and 46% flour yield was determined on average.The results of research in the literature indicate that there is a difference in the quality and yield levels of the cultivars used according to the region and conditions in which they are grown [19][20][21][22][23]. The energy value is an essential parameter in terms of the dough's resistance to processing and the degree of workability.…”
Section: Preparation Of Flour Blendsmentioning
confidence: 99%
“…Yıl ve hümik/fulvik asit uygulamalarının ortalamasına göre Krasunia Odeska çeşidi 358.1 kg da -1 tane verimi ile Renan (325.1 kg da -1 ) BŞEÜ Fen Bilimleri Dergisi çeşidinden daha yüksek değere sahip olmuştur (Tablo 4). Daha önceki yıllarda yapılan çalışmalar buğday da tane veriminin çeşide, bölgenin ekolojik yapısına ve uygulanan kültürel işlemlere göre değiştiğini göstermektedir [18][19][20][21][22][23]. Yapılan çalışmada buğday verimi gübresiz parsellerde 304.5 kg/da, dekara 1 lt hümik asit uygulanan parsellerde 406.15 kg/da, dekara 2 lt hümik asit uygulanan parsellerde 378.2 kd/da olarak belirlenmiştir [39].…”
Section: IIIunclassified